2018
DOI: 10.1111/ans.14441
|View full text |Cite
|
Sign up to set email alerts
|

Role of super‐selective embolization in lower gastrointestinal bleeding

Abstract: SSE was successful in a high proportion of patients in this series with low complication rates. Clinical success was higher in those who were older or with diverticular related bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Reported rate of bowel ischemia after embolization ranged from 0% to 22% in the literature[8,12,17]. In this study, no patient developed bowel infarction.…”
Section: Discussionmentioning
confidence: 48%
“…Reported rate of bowel ischemia after embolization ranged from 0% to 22% in the literature[8,12,17]. In this study, no patient developed bowel infarction.…”
Section: Discussionmentioning
confidence: 48%
“…[19] However, recent studies have shown that the incidence of serious ischemic complications of TAE for LGIB was very low (0–5.2%). [14,15] Such improvements in the incidence of AEs depend largely on technical advances such as the development of guide wires and catheter systems that enable super-selective embolization in TAE. Super-selective embolization of the nearest arcade of the vasa recta of the segmental branch is important to prevent TAE-related AEs, including intestinal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The technical success rate of TAE for LGIB is high, at 93% to 100%, and the rebleeding rate after TAE for CDB is low, at 13% to 14.3%. [13][14][15] TAE may thus offer a useful alternative method for achieving hemostasis in CDB with extravasation on CECT.…”
Section: Introductionmentioning
confidence: 99%
“…Patient related factors such as age, aetiology of bleed and comorbidities have proven important predictors of outcome in some studies. 11,12 Others have evaluated angiographic-related factors, demonstrating an association between negative angiographic findings and lower rebleeding rates, 13 and a higher rebleeding rate when embolisation was delayed, 14 and targeted over prophylactic embolisation leading to angiographic success. 15,16 Previous work examining the effects of treatment-related factors indicates that greater red blood cell transfusion requirements were associated with a higher rate of rebleeding.…”
Section: Introductionmentioning
confidence: 99%